1987
DOI: 10.1021/bi00399a063
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase converts purine riboside into an analog of a reactive intermediate: a carbon-13 NMR and kinetic study

Abstract: The 13C NMR spectra of [2-13C]- and [6-13C]purine ribosides have been obtained free in solution and bound to the active site of adenosine deaminase. The positions of the resonances of the bound ligand are shifted relative to those of the free ligand as follows: C-2, -3.7 ppm; C-6, -73.1 ppm. The binary complexes are in slow exchange with free purine riboside on the NMR time scale, and the dissociation rate constant is estimated to be 13.5 s-1 from the slow exchange broadening of the free signal. In aqueous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 33 publications
1
48
1
Order By: Relevance
“…34 If the mechanism is not changed in the presence of denaturant, then subtle conformational changes in the loop b2a2 around W117 and W161, even though they are distant from the catalytic reaction center, somehow affect the formation of the tetrahedral intermediate, presumably through conformational change propagated through the structure. The naturally occurring disease-related ADA mutants around the loop b2a2 provide an indirect support of our conclusion.…”
Section: Structural Mechanism Of Denaturant-induced Ada Inactivationmentioning
confidence: 99%
“…34 If the mechanism is not changed in the presence of denaturant, then subtle conformational changes in the loop b2a2 around W117 and W161, even though they are distant from the catalytic reaction center, somehow affect the formation of the tetrahedral intermediate, presumably through conformational change propagated through the structure. The naturally occurring disease-related ADA mutants around the loop b2a2 provide an indirect support of our conclusion.…”
Section: Structural Mechanism Of Denaturant-induced Ada Inactivationmentioning
confidence: 99%
“…It has been suggested that the enzyme undergoes a conformational change upon inhibitor binding (6,7) and that a reactive histidine group participates in catalysis of calf intestinal ADA (10). However, lack of sufficient quantities of human ADA has precluded detailed structural studies of important enzyme domains.…”
Section: Introductionmentioning
confidence: 99%
“…In humans deficiency of this purine salvage enzyme is associated with severe immunodeficiency and lymphopenia in both B-and T-cell lineages (1, 2 known about the enzymatic activity of human ADA, including its interaction with various substrates (4) and inhibitors (6-8), no direct information is available concerning the enzyme active site. Although a preliminary analysis of crystals of murine ADA has been reported (9), the three-dimensional fine structure of the human enzyme is not known.It has been suggested that the enzyme undergoes a conformational change upon inhibitor binding (6,7) and that a reactive histidine group participates in catalysis of calf intestinal ADA (10). However, lack of sufficient quantities of human ADA has precluded detailed structural studies of important enzyme domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the enzymatic mechanism the Zn 2+ polarizes a water molecule, which has hydrogen bonds to His238 and Asp295, and attacks the substrate to form a tetrahedral intermediate at the C6 position of the purine ring 1012,16. Zn 2+ binds to mADA tightly, with the dissociation constant estimated to be lower than 10 −9 M 17.…”
Section: Introductionmentioning
confidence: 99%